2013
DOI: 10.3109/10641955.2013.835820
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension, inflammation and T lymphocytes are increased in a rat model of HELLP syndrome

Abstract: Objective An animal model of hemolysis, elevated liver enzymes, low platelet count (HELLP) was used to determine if T lymphocytes accompany hypertension and increased inflammatory cytokines. Methods sFlt-1 (4.7 μg/kg/day) and sEndoglin (7 μg/kg/day) were infused into normal pregnant rats (HELLP rats) for 8 days. Results HELLP was associated with increased mean arterial pressure (p = 0.0001), hemolysis (p = 0.044), elevated liver enzymes (p = 0.027), and reduced platelets (p = 0.035). HELLP rats had increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(67 citation statements)
references
References 58 publications
4
63
0
Order By: Relevance
“…Similar to what was seen in placental secretion of ET-1, conditioned media from HELLP placentas did not significantly increase ET-1 production from HUVECs at either 6 hours (71. 21 …”
Section: Secretion Of Huvec Et-1 Is Increased When Exposed To Serum Fmentioning
confidence: 97%
“…Similar to what was seen in placental secretion of ET-1, conditioned media from HELLP placentas did not significantly increase ET-1 production from HUVECs at either 6 hours (71. 21 …”
Section: Secretion Of Huvec Et-1 Is Increased When Exposed To Serum Fmentioning
confidence: 97%
“…However, CD8 + T cells are associated with neuroinflammatory conditions such as neurological paraneoplastic syndromes and multiple sclerosis 15, 16 . As CD4 + and CD8 + T cells are increased in response to infusion of sFlt-1 and sEng 9, 10 we sought to determine if 1) rats with HELLP syndrome had an increase in BBB permeability and 2) if T cells contributed to the inflammation and any potential increase in BBB permeability in an animal model of HELLP syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…T lymphocytes are also thought to play a critical role in the pathogenesis of hypertension and vascular remodelling [9]. Recent data from experimental animal models found that T cells are associated with hypertension and inflammation [10]. It has been shown that potassium channels are essential for the activation of T lymphocytes, and that they are involved in multiple physiological processes, such as T lymphocyte differentiation, proliferation, and activation [11,12].…”
Section: Introductionmentioning
confidence: 99%